Hypoglycaemia – its causes and symptoms in the population of developmental age - Otto-Buczkowska, Ewa; Jainta, Natalia; Grzyb, Karolina (Pediatria Polska - Polish Journal of Paediatrics, 2018)
The amount of glucose in the circulation depends on its absorption from the intestine, uptake and release from the liver, and uptake by peripheral tissues. Insulin and glucagon together control the rate of metabolism required by peripheral tissues, and both are involved in maintaining glucose homeostasis. Insulin is considered to be an anabolic hormone that promotes the synthesis of protein, lipid, and glycogen. The key target tissues of insulin are: liver, muscle, and adipose tissue. Glucagon notably affects catabolic processes. Glucose is essential for cerebral metabolism. Unsurprisingly therefore, hypoglycaemia may result in encephalopathy. Knowledge of the homeostatic mechanisms that maintain blood glucose concentrations within a tight range is the key for diagnosis and appropriate management of hypoglycaemia. Young age, fasting, and severe infectious diseases are considered as important risk factors. Failure in investigating a neonate, infant, or a child with suspicion of hypoglycaemia, increases the risk of delaying a definitive diagnosis and instituting effective treatment. Expeditious identifying the specific cause of hypoglycaemia, as outlined above, will enable accurate institution of appropriate treatment and decrease the risk of permanent brain injury from persistent and recurrent severe hypoglycaemia. Prompt diagnosis with aggressive early intervention remains the mainstay of treatment to avert irreversible brain damage.